Assessment of the Dynamics of Experiencing a Terrorist Threat before and after the Terrorist Attack at Crocus City Hall - J.V. Bykhovets; N.N. Kazymova (Клиническая и специальная психология)
The article presents the results of a study on the experience of terrorist threat, psychological stress and anxiety among young girls aged 18-26 before and after a terrorist attack (two times were performed: three days and eight months later). It was shown that after the March 22, 2024 terrorist attack in Crocus City Hall, there was an increase in experience of the threat due to increased vigilance, alertness, anticipation of future attacks, concern for loved ones and need for information about attacks. Eight months after the attack, these indicators remained at the same level except for anticipation of new attacks (decrease was recorded). At the same time there were no changes in stress, anxiety or depression indicators. In addition, there has been an increase in hostility towards representatives of other nationalities, which may be related to the peculiarities of information coverage of events.